The range of large terrestrial mammals has expanded into human-dominated landscapes in Japan - Seung-Yun Baek; Tatsuya Amano; Munemitsu Akasaka; Shinsuke Koike (Communications Earth & Environment)
Abstract Large terrestrial mammals have generally declined due to human activity, but the recovery of some populations poses new issues for coexistence. Few studies to date have investigated drivers of this recovery and its impacts on human societies at the national scale. Here we assessed the range expansion of six large terrestrial mammal species over 40 years—sika deer, wild boar, Japanese serow, Japanese macaque, Asiatic black bear, and brown bear—by comparing newly occupied and unoccupied areas using distribution data in Japan. We found evidence that increased agricultural abandonment and decreased snowfall drove these range expansions. The range of all six species expanded from mountainous landscapes to those closer to human settlements, leading to increased conflicts that threaten people’s property and safety. We predict that accelerating depopulation and climate warming could further expand the range of these species, and call for measures to mitigate conflicts and achieve coexistence with them.